2010
DOI: 10.4102/sajip.v36i2.860
|View full text |Cite
|
Sign up to set email alerts
|

Validation of three Setswana measures for psychological wellbeing

Abstract: Orientation: From the perspective of positive psychology, it is important to evaluate people's strengths. There is, however, a lack of validated measures for these purposes in many of the South African official languages. As language is a medium for cultural meanings, measures of mental health should be validated in the mother tongue of the people involved.Research purpose: The aim of this study was therefore to explore the psychometric properties of Setswana versions of three measures of psychological wellbei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 70 publications
4
13
2
Order By: Relevance
“…South Africa has 11 official languages. A study by Wissing et al ( 45 ) describes language as the medium through which cultural meaning is created. It is recommended that future studies could consider validation of the WHOQOL-OLD modules in the mother tongue of the people involved.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa has 11 official languages. A study by Wissing et al ( 45 ) describes language as the medium through which cultural meaning is created. It is recommended that future studies could consider validation of the WHOQOL-OLD modules in the mother tongue of the people involved.…”
Section: Discussionmentioning
confidence: 99%
“…Test-retest reliability study yielded results of a 0.82 index, and a Cronbach alpha-reliability index of 0.87 (Diener et al 1985). Wissing et al (2010) who translated the SWLS into Afrikaans and Setswana also found it to be reliable and valid for use in South Africa. In the current study a Cronbach alpha coefficient of 0.74 was found for the SWLS.…”
Section: Satisfaction With Life Scale (Swls)mentioning
confidence: 95%
“…The authors, however, acknowledged the independence of positive and negative affect and cautioned that in some circumstances it might be useful to score the positive and negative subscales separately. On the contrary, a two-factor solution (AFM-PA and AFM-NA) was reported after CFA and EFA were applied to a dataset collated from a sample of Setswana-speaking South Africans [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Presently, there is a general lack of research that investigates the evidence for the validity of the Twi version of mental health and well-being measurement instruments in Ghana, particularly in a rural poor context. The selected measurement instruments have shown promise in previous African studies [ 21 23 , 47 , 49 ], are all relatively short, and together assess facets relevant to the evaluation of mental health and well-being in the African context. The selection of these measures was also supported by the growing research evidence that suggests that the complete evaluation of mental health and well-being should also be complemented by the assessment of negative experiences and emotional states [ 9 ], considering the complex interactions between positive aspects of human functioning and negative experiences [ 8 , 9 ] that, together, influence thinking patterns, feelings, and behavior of people.…”
Section: General Methodsmentioning
confidence: 99%